How information on sexism may increase women's perceptions of being excluded, threaten fundamental needs, and lower career motivation. (18th April 2022) - Doolaard, Frank T.; Lelieveld, Gert‐Jan; Noordewier, Marret K.; van Beest, Ilja; van Dijk, Eric
Abstract: The current research investigates the effects of exposure to information about the prevalence of sexism in society on women's perceptions, needs, expectations, and career motivation. We propose that such exposure to sexism prevalence may threaten women's fundamental need to belong, and induces perceptions of social exclusion. Study 1 provided correlational evidence that perceiving society as sexist relates to increased perceptions of being excluded. Three experimental studies demonstrated that exposure to information about sexism in the form of fictional research results (Study 2), or actual newspaper articles (Studies 3 and 4), increased women's experiences of social exclusion. Exposure to such information also lowered women's gender‐related expectations of achieving their preferred position in society, and reduced career motivation. Together, the article provides insight into the experiential and motivational reactions to sexism in society.